Biliary ascariasis – A vicious cycle - Nurfariza Che Husin (Academy of Family Physicians of Malaysia, 2021)
Biliary ascariasis is a rare disease in a non-endemic area. However, it is one of the possible etiological factors for retarded growth as well as malnutrition in children. It may cause intestinal obstruction, appendicitis, biliary obstruction, liver abscess, hepatolithiasis, and pancreatitis in adults. Herein, we report a patient with ascending cholangitis secondary to biliary ascariasis who was successfully managed with Endoscopic Retrograde Cholangio Pancreaticography.